2004
DOI: 10.1364/opex.12.004847
|View full text |Cite
|
Sign up to set email alerts
|

Iridescence of a shell of mollusk Haliotis Glabra

Abstract: Pearls and shells of some mollusks are attractive inorganic materials primarily owing to the beauty of their natural lustrous and iridescent surface. The iridescent colors can be explained by diffraction or interference or both, depending on the microstructure of the surface. Strong iridescent colors are very evident on the polished shell of the mollusk Haliotis Glabra, commonly known as abalone. It would be interesting to study how these colors are produced on the surface of the shell. By using a scanning ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
60
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 3 publications
0
60
0
Order By: Relevance
“…[72,73]) report similar groove structures on polished shell surfaces of Pinctada margaritifera and Haliotis glabra (Fig. 8) respectively.…”
Section: Optical Properties Of Nacrementioning
confidence: 67%
“…[72,73]) report similar groove structures on polished shell surfaces of Pinctada margaritifera and Haliotis glabra (Fig. 8) respectively.…”
Section: Optical Properties Of Nacrementioning
confidence: 67%
“…[26][27][28] From an optical standpoint, nacre has been studied to better understand the unique colors in terms of diffraction from fine-scale grating structures on the shell surface and interference from the inner nacreous layers. [29][30][31] In particular, photonic band states, which imply perfect ordered nanostructures, are speculated to play an important role in the distinct colors of abalone shells and pearls. 32,33 However, these unique nanostructures of nacre have not yet been exploited as optical resonators.…”
Section: Introductionmentioning
confidence: 99%
“…Many artifices are employed by creatures to display metallic-like colors as signals, defending against predators, and camouflage [1][2][3]. Mäthger et al [4] studied the Paradise whiptail (Pentapodus paradiseus) and found that it has distinct reflective stripes on its head and body.…”
mentioning
confidence: 99%